Hubungan Masa Kerja Perawat Dengan Kepatuhan Pelaksanaan SPO Pencegahan Resiko Jatuh Pada Pasien Di Ruang Rawat Inap RS TK. II Robert Wolter Mongisidi - Fadilah Junita Kanja; Zainar Kasim; Silvia Dewi M. Riu (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Work period is part of the workforce characteristic factors that make a person's behavior more familiar with the conditions of the workplace environment based on the length of work, if nurses are familiar with the environmental conditions of the workplace and the dangers of their work both for themselves and others, the workforce will comply with the safety of themselves and others, especially in preventing patient falls. The purpose of this study is to determine the relationship between nurses work period and compliance with the implementation of Standard Procedures Operational (SPO) fall risk in the inpatient room at TK II Robert Wolter Mongisidi Hospital. The method used in this study is descriptive correlational with a cross sectional approach. The sample obtained was 33 subjes using total sampling technique. Data collection uses observation sheets. Data was analysist used the Chi Square test with a level of significance (α < 0.05). The results of chi square test obtained a value of ρ = 0.203 ​​(ρ > 0.05). This means that there is no significant relationship between nurses work period and compliance with the implementation of Standard Procedures Operational (SPO) fall risk in the inpatient room at TK II Robert Wolter Mongisidi Hospital. The conclusion from this study there is no relationship between the nurses work period and compliance with the implementation of Standard Procedures Operational (SPO) fall risk in the inpatient room at TK II Robert Wolter Mongisidi Hospital. Suggestions can be used as a source of information regarding the relationship between nurses work period and compliance with the implementation of Standard Procedures Operational (SPO) fall risk.